1987
DOI: 10.1111/j.1476-5381.1987.tb11391.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of amiloride analogues on prostacyclin synthesis by rat aortic rings

Abstract: 1 Fresh rat aortic rings were incubated in HEPES-buffered salt solutions (pH 8.0) in the presence or absence of amiloride analogues. The effect of these drugs on prostacyclin (PGI2) synthesis was determined by radioimmunoassay of the stable hydrolysis product 6-oxo-prostaglandin (PG)FIm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Prostacyclin, another endothelial vasodilator has previously been ruled out to account for amiloride-induced vascular relaxation and to be stimulated by amiloride. 24,25 The fact that plasma NO-products were not altered in mice treated by amiloride and benzamil and that blood pressure drop was maintained after L-NAME administration and in eNOS −/− together supports that amiloride lowered blood pressure independent of NOS. Impaired responsiveness to acetylcholine confirmed that endothelial NO formation was attenuated in both eNOS −/− and L-NAME-treated mice.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Prostacyclin, another endothelial vasodilator has previously been ruled out to account for amiloride-induced vascular relaxation and to be stimulated by amiloride. 24,25 The fact that plasma NO-products were not altered in mice treated by amiloride and benzamil and that blood pressure drop was maintained after L-NAME administration and in eNOS −/− together supports that amiloride lowered blood pressure independent of NOS. Impaired responsiveness to acetylcholine confirmed that endothelial NO formation was attenuated in both eNOS −/− and L-NAME-treated mice.…”
Section: Discussionmentioning
confidence: 83%
“…However, the concentrations of amiloride in the cited in vivo and ex vivo studies reached levels (>500 nmol/L) where amiloride also targets Na + /H + exchangers and α‐and β‐adrenoceptors that could confound interpretation of the observed vasodilator effect. Prostacyclin, another endothelial vasodilator has previously been ruled out to account for amiloride‐induced vascular relaxation and to be stimulated by amiloride . The fact that plasma NO‐products were not altered in mice treated by amiloride and benzamil and that blood pressure drop was maintained after L‐NAME administration and in eNOS −/− together supports that amiloride lowered blood pressure independent of NOS.…”
Section: Discussionmentioning
confidence: 91%
“…In vitro studies indicate that the amiloride analog phenamil is a highly specific inhibitor of Na ϩ channels, such as epithelial sodium channels (ENaCs) and acid-sensing ion channels (ASICs) (38). Our results show that downregulation of ASIC protein 1 (ASIC1) or ASIC3 by siRNA elevates Trb3 expression and facilitates BMP-mediated contractile activities, while downregulation of ENaC has no effect, which suggests that inhibition of ASIC1 and ASIC3 by phenamil is critical for induction of Trb3.…”
Section: Discussionmentioning
confidence: 99%
“…We used 5-(N,N-hexamethylene)amiloride to investigate whether Na+/H+ exchange is implicated in the bradykinin receptor-effector linkage in rabbit coeliac artery. This drug is a potent inhibitor of Na+/H+ exchange (Simchowitz & Cragoe, 1986) that inhibits Ca2'-stimulated PGI2 synthesis by rat aorta (Ritter et al, 1987a). We also studied ibuprofen, to determine the effect of this cyclo-oxygenase inhibitor on the mechanical response.…”
Section: Introductionmentioning
confidence: 99%